Strengthening Social Education in the Development of Caregivers for the Elderly for the Global Market: A Collaborative Model for Poverty Alleviation - Supomo Supomo (Green Publisher Indonesia, 2026)
The increase in the elderly population globally and nationally encourages the need for professional caregivers while opening up strategic opportunities in poverty alleviation. This research aims to formulate a model for strengthening social counselling in the development of elderly caregivers that is integrated with the needs of the global market through a collaborative approach. This study used a qualitative approach with literature study and policy analysis methods, with reference to the theoretical framework of Ansell and Gash as well as studies related to the long-term care workforce. The results of the study show that strengthening social counselling needs to be built through four main pillars, namely the identification of vulnerable human resources, mindset transformation, the internalization of empathy values, and the strengthening of social readiness. Social counselling does not only function as a knowledge transfer, but as a transformative instrument in building social and professional competence. The successful implementation of the model is highly dependent on collaborative governance involving the Ministry of Social Affairs, the Ministry of Manpower, certification bodies, the private sector, non-governmental organizations, and liaison actors. The integration of social counselling with the caregiver development system and collaboration was able to produce two main findings, namely meeting the needs of global caregivers and overcoming national poverty through the creation of jobs based on social competence.